Erythrocytes of the common carp are immune sentinels that sense pathogen molecular patterns, engulf particles and secrete pro-inflammatory cytokines against bacterial infection - Majstorović, Jovana; Kyslík, Jiří; Klak, Katarzyna; Maciuszek, Magdalena; Chan, Justin T. H.; Korytář, Tomáš; Holzer, Astrid S. (Frontiers in Immunology, 2024)
Red blood cells (RBCs), also known as erythrocytes, are underestimated in their role in the immune system. In mammals, erythrocytes undergo maturation that involves the loss of nuclei, resulting in limited transcription and protein synthesis capabilities. However, the nucleated nature of nonmammalian RBCs is challenging this conventional understanding of RBCs. Notably, in bony fishes, research indicates that RBCs are not only susceptible to pathogen attacks but express immune receptors and effector molecules. However, given the abundance of RBCs and their interaction with every physiological system, we postulate that they act in surveillance as sentinels, rapid responders, and messengers. We performed a series of in vitro experiments with Cyprinus carpio RBCs exposed to Aeromonas hydrophila, as well as in vivo laboratory infections using different concentrations of bacteria. qPCR revealed that RBCs express genes of several inflammatory cytokines. Using cyprinidspecific antibodies, we confirmed that RBCs secreted tumor necrosis factor alpha (TNFα) and interferon gamma (IFNγ). In contrast to these indirect immune mechanisms, we observed that RBCs produce reactive oxygen species and, through transmission electron and confocal microscopy, that RBCs can engulf particles. Finally, RBCs expressed and upregulated several putative toll-like receptors, including tlr4 and tlr9, in vivo in response to A. hydrophila infection. Overall, the RBC repertoire of pattern recognition receptors, their secretion of effector molecules, and their swift response make them immune sentinels capable of rapidly detecting and signaling the presence of foreign pathogens. By studying the interaction between a bacterium and erythrocytes, we provide novel insights into how the latter may contribute to overall innate and adaptive immune responses of teleost fishes.